2021
DOI: 10.1007/s11764-021-01069-9
|View full text |Cite
|
Sign up to set email alerts
|

“Every day is just kind of weighing my options.” Perspectives of young adult cancer survivors dealing with the uncertainty of the COVID-19 global pandemic

Abstract: Purpose We explored adolescent and young adult cancer survivor (AYA) experiences with COVID-19 to understand the impact of living through a pandemic, unmet needs, and coping strategies. Methods AYAs were recruited nationally, completed an online survey, and attended one of six online focus groups. We used qualitative content analysis to analyze focus group data. Results Thirty-nine AYAs completed the survey, and 24 also participated in the fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 19 publications
1
14
0
1
Order By: Relevance
“…Studies used many different outcome measures in their cross-sectional designs ( Table 1 ). Six studies employed a qualitative methodology [23] , [24] , [25] , [26] , [27] , [28] and four study used mixed methods [29] , [30] , [31] , [32] .…”
Section: Resultsmentioning
confidence: 99%
“…Studies used many different outcome measures in their cross-sectional designs ( Table 1 ). Six studies employed a qualitative methodology [23] , [24] , [25] , [26] , [27] , [28] and four study used mixed methods [29] , [30] , [31] , [32] .…”
Section: Resultsmentioning
confidence: 99%
“…For some, their cancer experience may serve as a buffer against some of the risks of the pandemic. A qualitative study conducted by Shay et al (2021) with AYA patients and survivors identified perceived unexpected advantage of a cancer history during the early stages of the global pandemic. Specifically, AYA survivors relied on strategies that they previously used to cope with their cancer and treatment.…”
Section: Discussionmentioning
confidence: 99%
“…AYA survivors may be at a greater risk of mental health concerns given their health history and perceived vulnerabilities. Indeed, a mixed-methods study conducted in the United States at the outset of the pandemic found that AYA survivors reported a high level of anxiety regarding their health and that of their family, feelings of isolation, and worries about employment status (Shay et al, 2021). In another international study comprised of AYA patients and survivors, more than 50% of respondents expressed an interest for information tailored to their needs in coping with the pandemic (Košir et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Potential drivers of observed increases in psychological distress may be related to lifestyle changes, including social isolation, economic disruptions, and uncertainty about the future. For YACS, this may be heightened with the pandemic’s effects on cancer care delivery (e.g., diagnostic or treatment delays, drug shortages, or move to telehealth appointments) and fear of increased susceptibility to severe COVID-19 among cancer survivors (Nekhlyudov et al, 2020; Saini et al, 2020; Shay et al, 2021). Research is needed on YACS’ risk and resilience factors that could ultimately impact future health and QOL.…”
Section: Discussionmentioning
confidence: 99%
“…Nearly 84,000 young adults (YAs; ages 20–39 at diagnosis) are diagnosed with cancer each year in the United States (Miller et al, 2020). Even before the pandemic, YA cancer survivors (YACS) faced a “new normal” related to pre- and post-cancer diagnosis; the pandemic brought another experience of uncertainty early in the life course (Donovan et al, 2015; Shay et al, 2021). YAs represent a unique population of cancer survivors, often in-between pediatric and adult oncology care settings (Janardan & Wechsler, 2021; Zebrack et al, 2014), and face a significant health crisis at a time marked by meeting major personal, school, and work milestones (D’Agostino et al, 2011).…”
mentioning
confidence: 99%